Analisis Ketersediaan Air Irigasi dan Kebutuhan Air Irigasi Menggunakan Software Cropwat Version 8.0 - Andre Fatahillah; Meliyana Meliyana; Ichsan Syahputra; Amri Amin; Cut Rahmawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The balance between availability and demand for water is an important factor determining the productivity of a plant. Imbalance between water availability and water demand can reduce productivity or even crop failure. The main water source that irrigates the Pandrah Irrigation Area comes from the Krueng Pandrah River located in Bireuen Regency, Aceh Province. The Krueng Pandrah watershed has a total area of about 127.24 km2 and has a main river length of 44.37 km. This study aims to determine the amount of irrigation water needed by plants and the available water discharge to meet crop water needs so as to improve the quality of community harvests, especially in Pandrah District, Bireuen Regency. In this study, the calculation of water requirements was carried out using Cropwat version 8.0 software. Cropwat software is an FAO program that is very practical to use to determine the value of plant water needs and irrigation water needs. In determining the 80% reliable discharge, the FJ Mock method is used as a reference to calculate the value of water availability. To find out the value of the water balance between the two, a water balance analysis was carried out. From the research results, it is known that the maximum water demand is 1,694 m3/sec and the minimum water requirement is 1,238 m3/sec. As for the available water to meet the water needs of plants, it is known that the maximum mainstay discharge is 3.46 m3/sec and the minimum reliable discharge is 2.27 m3/sec. From the results obtained and after analyzing the water balance, it is known that the Krueng Pandrah watershed is in a condition of surplus water. Where the water needed by plants can be met properly by available water without deficit during planting. The value between water demand and the availability of existing water has reached a waterbalance so as to avoid crop failure for the community in the Pandrah irrigation area, Bireuen Regency.